Analisis Ketepatan Resep Obat Berdasarkan Formularium Nasional pada Pasien Rawat Jalan Rumah Sakit Umum Pelaihari - Rahmah, Aulia; Pratiwi, Desy; Putri, Indah Pebriani; Mulia, Radha Eka; Sari, Okta Muthia; Rahmatullah, Satrio Wibowo; Setiawan, Deni; Apriyanti, Anna (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
The National Formulary serves as a tool for controlling the quality of drug use in healthcare facilities. In accordance with the National Hospital Service Quality Indicators, drug prescriptions must follow the guidelines set by the National Formulary, which is continuously updated, including the 2020 edition. This study aims to calculate the percentage of prescription accuracy based on the restrictions outlined in the 2020 National Formulary for outpatients. This retrospective study was conducted at Pelaihari General Hospital. The study population included all outpatient prescriptions issued during October 2022 that met the inclusion criteria. Prescription accuracy was analyzed by referring to the 2020 National Formulary. The results showed that 80.91% of prescribed medications were in accordance with the 2020 National Formulary. The average accuracy of prescriptions based on the restrictions in the 2020 National Formulary was 99.79%, with 99.84% accuracy in indication restrictions and 99.75% accuracy in prescriber authority restrictions.